2011
DOI: 10.1371/journal.pone.0019391
|View full text |Cite
|
Sign up to set email alerts
|

Versatility of MicroRNA Biogenesis

Abstract: MicroRNAs (miRNAs) are short single-stranded RNA molecules that regulate gene expression. MiRNAs originate from large primary (pri) and precursor (pre) transcripts that undergo various processing steps along their biogenesis pathway till they reach their mature and functional form. It is not clear, however, whether all miRNAs are processed similarly. Here we show that the ratio between pre-miRNA and mature miRNA forms varies between different miRNAs. Moreover, over-expression of several factors involved in miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 18 publications
2
37
0
Order By: Relevance
“…In addition to regulating the expression of different genes post-transcriptionally, NF90 also takes part in miRNA biogenesis. As a competitor for the association of the microprocessor complex with pri-miRNAs, NF90 usually inhibits miRNA production (27,41,42). We found that lncRNA-LET depletion resulted in elevated level of NF90 which in turn blocks miR-145 biogenesis by competitively binding to pri-miR-145 specifically.…”
Section: Discussionmentioning
confidence: 83%
“…In addition to regulating the expression of different genes post-transcriptionally, NF90 also takes part in miRNA biogenesis. As a competitor for the association of the microprocessor complex with pri-miRNAs, NF90 usually inhibits miRNA production (27,41,42). We found that lncRNA-LET depletion resulted in elevated level of NF90 which in turn blocks miR-145 biogenesis by competitively binding to pri-miR-145 specifically.…”
Section: Discussionmentioning
confidence: 83%
“…However, the biological relevance of these changes still needs to be investigated and fully elucidated. Indeed, we have to take into account that QPCR analyses of the specific mature microRNA might be underestimated, considering that the inherent stability of the specific microRNA may be affected by cell activity and stimulation (57,58). Furthermore, the effect of DA on miR-29a regulation also may be the consequence of other molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of Drosha as a target enzyme was on the basis of the knowledge that Drosha activity is restricted to the generation of miRNAs. [25][26][27] Here, we reported that depletion of Drosha in MSCs generated EVs with a deregulation of their miRNA content and altered the intrinsic regenerative potential of MSCs and derived EVs. These data support the relevance of miRNAs shuttled by EVs in the healing properties of MSCs.…”
mentioning
confidence: 91%